Uma contribuição ao aprimoramento do instituto da compensação ambiental previsto na lei 9.985/2000 - Bechara, Erika (2007)
On behalf of the principle of the sustainable development, all workmanships and activities that potentially cause environmental degradation must be adjusted to effective environment standards, aiming to eliminate its degrading potential or at least mitigate it, as much as permitted by available technology and scientific knowledge. The technology and knowledge on elimination and reduction of environmental damage, however, do not reach all the array of projects and activities. Even so, the need of executing such projects and activities can demand their accomplishment despite environment impacts which can not be eliminated or mitigated. In this in case that, such impacts will have to be counterbalanced by the entrepreneur, so that the commitment to the basic right to the environmental health, as a result of "the needed" activity, to be either compensated with an ambient benefit, so that it reduces a loss with a profit, thus reaching a balance situation. Guided for this premise the legislator created the institute of environmental compensation, currently ruled by Law 9.985/2000. It is about the mechanism to compensate environmental damages of one given to workmanship or activity, identified in the environment licensing - therefore previous to the implantation of the degrading activity. Because it is a mechanism surrounded of controversy and questionings even with regards to its constitutionality, its acceptance in the legal world depends on the understanding of all the aspects related to it, and, eventually, of a revision of its legal regimen. The present work intends to analyse the details of legal nature of environmental compensation and its legal framework for, at the end, eliminate doubts and baseless resistence and, as for the based doubts suggest the improvement of legal rule of the instrument, to conform it to constitutional premises and give it full applicability